2022
DOI: 10.3389/fpubh.2022.1061328
|View full text |Cite
|
Sign up to set email alerts
|

Noise annoyance and risk of prevalent and incident atrial fibrillation–A sex-specific analysis

Abstract: BackgroundWhile chronic exposure to high levels of noise was demonstrated to increase the risk of various cardiovascular diseases, the association between noise annoyance and risk of cardiovascular disease remains still inconsistent. Recently, we showed that noise annoyance is associated with prevalent atrial fibrillation in the general population. However, the association between noise annoyance and risk of incident atrial fibrillation as well as potential sex-differences remain still elusive.Methods and resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This, in turn, generates the development and acceleration of cardiovascular risk factors such as arterial hypertension, arrhythmia, dyslipidemia, increased blood viscosity and blood glucose, and activation of blood clotting factors, finally leading to manifest cardiovascular disease over time. In line, we have recently shown that noise annoyance due to different sources is associated with a higher risk of prevalent and incident atrial fibrillation in the Gutenberg Health Study (GHS), including 15,010 participants [ 3 5 ]. A further study based on data from the GHS also revealed that noise annoyance due to different sources was associated with increased midregional pro-atrial natriuretic peptide levels, a marker that is associated with endothelial function, which in turn was predictive of incident atrial fibrillation and cardiovascular disease as well as all-cause mortality [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, generates the development and acceleration of cardiovascular risk factors such as arterial hypertension, arrhythmia, dyslipidemia, increased blood viscosity and blood glucose, and activation of blood clotting factors, finally leading to manifest cardiovascular disease over time. In line, we have recently shown that noise annoyance due to different sources is associated with a higher risk of prevalent and incident atrial fibrillation in the Gutenberg Health Study (GHS), including 15,010 participants [ 3 5 ]. A further study based on data from the GHS also revealed that noise annoyance due to different sources was associated with increased midregional pro-atrial natriuretic peptide levels, a marker that is associated with endothelial function, which in turn was predictive of incident atrial fibrillation and cardiovascular disease as well as all-cause mortality [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noise can also increase the risk of mental disorders such as depression, anxiety disorders, psychoses and suicide. 95 These place effects and other different potential causal factors need to be considered in future studies. Proximity to roads, for example, is also used as a proxy for air pollution exposure and noise.…”
Section: Methodological Issues In Air Pollution and Mental Health Res...mentioning
confidence: 99%
“…The analysis revealed consistent and positive associations between noise annoyance and prevalent incident AF in men, while the association was weaker in women, particularly for incident AF. 53 A Danish study involving female nurses investigated the relationship between road traffic noise, air pollution, and AF incidence. The findings indicated that long-term exposure to higher levels of road traffic noise was associated with an increased risk of AF.…”
Section: Noise Pollutionmentioning
confidence: 99%